THE STRATEGIC NEED OF THE NATIONAL IDEA IN ENSURING THE STABILITY OF THE STATE AND SOCIETY (Conferencea, 2022)
At the higher stages of the development and improvement process, society acquires the appearance of a complex system consisting of authorities and governing bodies covering many social rules and groups. The components of society are reminiscent of a comprehensive social organism that is closely connected with each other both horizontally and vertically. During this period, it is important for the society to ensure its stability, security and development.